Intensity-Modulated Radiation Therapy with Stereotactic Body Radiation Therapy Boost for Unfavorable Prostate Cancer: The Georgetown University Experience - Mercado, Catherine; Kress, Marie-Adele; Cyr, Robyn A.; Chen, Leonard N.; Yung, Thomas M.; Bullock, Elizabeth G.; Lei, Siyuan; Collins, Brian T.; Satinsky, Andrew N.; Harter, K. William; Suy, Simeng; Dritschilo, Anatoly; et al. (Frontiers in Oncology, 2016)
Abstract: Purpose/Objective(s): Stereotactic body radiation therapy (SBRT) is emerging as a minimally invasive alternative to brachytherapy to deliver highly conformal, dose-escalated radiation therapy to the prostate. SBRT alone may not adequately cover the tumor extensions outside the prostate commonly seen in unfavorable prostate cancer. External beam radiation therapy (EBRT) with high dose rate brachytherapy boost is a proven effective therapy for unfavorable prostate cancer. This study reports on early PSA and prostate cancer specific quality of life outcomes in a cohort of unfavorable patients treated with intensity modulated radiation therapy (IMRT) and SBRT boost. Materials/Methods: Prostate cancer patients treated with SBRT (19.5 Gy in 3 fractions) followed by fiducial-guided IMRT (45-50.4 Gy) from March 2008 to September 2012 were included in this retrospective review of prospectively collected data. Biochemical failure was assessed using the Phoenix definition. Patients completed the Expanded Prostate Cancer Index Composite (EPIC)-26 at baseline, one month after the completion of radiation therapy (RT), every 3 months for the first year, then every six months for a minimum of two years. Results: One hundred and eight patients (4 low-, 45 intermediate- and 59 high-risk) with median age of 74 years completed treatment, with median follow-up of 4.4 years. Sixty four percent of the patients received ADT prior to the initiation of RT. The 3-year actuarial biochemical control rates were 100% and 89.8% for intermediate- and high-risk patients, respectively. At the initiation of RT, 9% and 5% of men felt their urinary and bowel function was a moderate to big problem, respectively. Mean EPIC urinary and bowel function and bother scores exhibited transient declines, with subsequent return to near baseline. At 2 years post-treatment, 13.7% and 5% of men felt their urinary and bowel function was a moderate to big problem, respectively. Conclusion: At 3 year follow-up, biochemical control was favorable. Acute urinary and bowel symptoms were comparable to conventionally fractionated IMRT and brachytherapy. Patients recovered to near their baseline urinary and bowel function by 2 years post-treatment. A combination of IMRT with SBRT boost is well-tolerated with minimal impact on prostate cancer specific quality of life.